1967
DOI: 10.2514/3.3914
|View full text |Cite
|
Sign up to set email alerts
|

Pressure dependence of hybrid fuel regression rates.

Abstract: Previously published data for nonmetalized and metalized fuels exhibited a strong dependence on oxidizer flow rate and burner pressure. In this study, the observed pressure dependence was investigated further. Butyl rubber, lithium hydride, and polyurethane fuels were investigated using a laboratory slab burner; the gaseous oxidizers were fluorine, oxygen, and nitrogen. Using oxygen or nitrogen as a diluent, the partial and total pressures of fluorine were varied independently from 4 to 130 psi and 20 to 165 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
1

Year Published

1974
1974
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 4 publications
0
13
0
1
Order By: Relevance
“…Although their early studies showed an enhancement of the regression rate with increasing pressure (assuming a fixed value of the local mass flow), the authors failed to find a satisfactory theoretical explanation for the results. In a subsequent work [4], the authors conjectured that this cause was to be found in the presence of oxygen at the solid surface. That led to the occurrence of heterogeneous reactions between the solid fuel and the surrounding gaseous oxygen, making the solid interface more reactive.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although their early studies showed an enhancement of the regression rate with increasing pressure (assuming a fixed value of the local mass flow), the authors failed to find a satisfactory theoretical explanation for the results. In a subsequent work [4], the authors conjectured that this cause was to be found in the presence of oxygen at the solid surface. That led to the occurrence of heterogeneous reactions between the solid fuel and the surrounding gaseous oxygen, making the solid interface more reactive.…”
mentioning
confidence: 99%
“…One of the major conclusions was that the assumed dependence on the chamber pressure, increased as the local specific mass flux increased. However, even though several arguments were proposed in favor of this hypothesis [4], a proved explanation for the witnessed behavior was still missing. One of the rejected explanations regarded the radiative heat flux increase with pressure.…”
mentioning
confidence: 99%
“…This effort entailed the development of an analytical expression for the regression rate as a function of several kinetic parameters and length-scales. Miller [20] developed a model that incorporated both the fuel diffusion rate and the chemical reaction rates, which he used to successfully correlate data taken by Smoot and Price [21][22][23]. Kosdon and Williams [24] later noted that Miller's analysis was only applicable to systems with low pressure and moderate oxidizer fluxes and derived a new expression that incorporated a flame zone of finite thickness.…”
Section: Kinetics-limited Modelsmentioning
confidence: 99%
“…Another group of researchers focused more on heterogeneous surface reactions as the source of kinetics dependence. Smoot and Price [21][22][23] performed numerous tests using a slab burner and found that, above a threshold value of G, the regression rate became nearly independent of G and instead varied with P and the oxidizer composition. These researchers defined a low mass flux regime where the normal G 0.8 dependence held, an intermediate mass flux regime where both P and G played a role, and a third regime at very high mass fluxes where the regression rate varied with pressure, as in the case of a solid rocket propellant; namely,ṙ ∝ P n .…”
Section: Kinetics-limited Modelsmentioning
confidence: 99%
“…The fuel regression rate referred to as the rate the fuel surface recedes is a key parameter for the hybrid rocket motor design. A lot of research efforts [1][2][3][4][5][6][7] have been conducted to find out the optimum expression for the regression rate. Among such efforts, Marxman et al [8][9][10] derived a functional relation commonly known as the "local regression rate law" for the hybrid rocket combustion.…”
mentioning
confidence: 99%